The Influence of Thermal Load on Composite Coating PTFE - Lysoňková, Irena; Svobodová, Jaroslava; Lattner, Michal (Manufacturing Technology Journal, 2018)
This article deals with the thermal stability of the PTFE coating and the composite coating composed with the PTFE matrix and titanium dioxide particles. These coatings have application in production of aluminium moulds in the automotive industry, specifically in the vulcanization of rubber materials. The first type of coating (PTFE coating) is already applied in the production and thanks to its application on the Al mould surface, the maintenance interval was increased by up to 400% compared to the uncoated state. Vulcanization of rubber compounds usually take place at a temperature 150 - 170°C. This temperature can be increased after addition of additives to a temperature 220°C. For this reasons, there is the research focused on degradation of these coatings at various thermal loads. Thermal stability was tested on coatings - PTFE a PTFE + TiO2 - applied on aluminium substrate (type Al - Si). Experimental samples were loaded at temperatures 150°C, 200°C, 250°C, 300°C, 350°C, 400°C a 500°C at a time 30 minutes and 60 minutes. The samples after thermal load were performed to tribometric analysis, and to the surface roughness measurement of selected parameters. The samples were also evaluated from the point of view of surface morphology and state of the surface with SEM and EDS analysis.
Keywords: Surface Pre-treatment; PTFE Coating; Composite Coating; Coefficient of Friction; Thermal Stability